Molecular characterization of BRCA1 as candidate gene marker for subclinical mastitis in Dairy water buffaloes (Bubalus bubalis) - Biendima, Cyndi C.; Uy, Mary Rose D.; Mingala, Claro N. (2017)
Subclinical mastitis (SCM), a major problem in dairy animals all over the world, is caused by intramammary infections with coagulase-negative staphylococci. It causes enormous losses for breeders since it suppresses the milk yield and quality; hence, it influences the national income of the country. It is related to low milk production, altered milk consistency, low protein content and high risk of contamination due to pathogenic organisms. The goal of the present study is to discover new information about the gene of interest, breast cancer 1 (BRCA1), early onset in the water buffalo genome by examining the presence of single nucleotide polymorphisms (SNPs) in water buffaloes. DNA from milk samples was isolated from thirty female riverinetype water buffaloes. Somatic cell score (SCS) was calculated from somatic cell count for each sample. The results showed two animals reached greater than 5, 5.6 and 5.8 SCS, respectively, which is indicative of SCM infection. Multiple sequence alignment revealed that all samples were monomorphic for BRCA1 gene. The genetic homology is undeniably high; however, it is not conclusive that the polymorphism found in cattle can also be found in water buffaloes. It is recommended that other single nucleotide polymorphisms in other exon should be studied. Also, the search for other candidate genes and larger sample size are essential to fully understand if these polymorphisms really affect the susceptibility of animals to SCM. (Author's abstract)